Missing the tide? Workplace cultural differences as a barrier to seafarer mobility in the U.S. workboat and sail training sectors. Issue 7 (2nd October 2016) - Romelczyk, Eric; Becker, Austin
ABSTRACT: While previous research details the psychological and social benefits of sail training programs for amateur 'trainees, ' much less is known about the value and transferability of sail training work experience in terms of professional development for seafaring careers. This article reviews the current state of scientific knowledge on sail training and presents the findings of a qualitative study of maritime recruiter perceptions at 10 U.S. flag workboat companies. Results suggest that the maritime industry may benefit from an improved understanding of the role that sail training programs and the sail training community can play in training and inspiring the next generation of motivated and professional seafarers. Workboat recruiters see positive and negative aspects of sail training experience and perceive cultural divides within the maritime industry that may affect a seafarers' job mobility, whether or not such divides actually exist.